2003
DOI: 10.1016/s0149-2063(03)00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Inverted U-Shaped Relationship Between Time and Performance: Meta-Analyses of the Experience/Performance, Tenure/Performance, and Age/Performance Relationships

Abstract: Theoretical and empirical research suggests that job experience, organizational tenure, and age have nonlinear relationships with performance. Considered simultaneously, there should exist an inverted Ushaped relationship between time and performance. Furthermore, the nature of this inverted U-shaped relationship should be affected by characteristics of the sample and measurement of performance. Using meta-analysis, this paper seeks to confirm the existence of the inverted U-shaped relationship between time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
379
1
20

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(427 citation statements)
references
References 205 publications
21
379
1
20
Order By: Relevance
“…It is also possible that there is error in measurements of the independent or dependent variable in the studies we reviewed. While some scholars make use of estimates for population reliabilities (Combs/Ketchen Jr. 2003, Sturman 2003, other researchers assume global reliabilities of 0.80 in measuring the independent and dependent variable in their metaanalyses (Dalton/Daily/Ellstrand/Johnson 1998, Dalton et al 1999, King/Dalton/ Daily/Covin 2004. However, we could not accurately account for measurement error, as none of our articles reported information on data reliability.…”
Section: Discussionmentioning
confidence: 91%
“…It is also possible that there is error in measurements of the independent or dependent variable in the studies we reviewed. While some scholars make use of estimates for population reliabilities (Combs/Ketchen Jr. 2003, Sturman 2003, other researchers assume global reliabilities of 0.80 in measuring the independent and dependent variable in their metaanalyses (Dalton/Daily/Ellstrand/Johnson 1998, Dalton et al 1999, King/Dalton/ Daily/Covin 2004. However, we could not accurately account for measurement error, as none of our articles reported information on data reliability.…”
Section: Discussionmentioning
confidence: 91%
“…This information was evaluated as a multi-group analysis, with the results indicating the factorial structural model was invariant (equivalent, with no significant differences) across the worker-periods. It is interesting to note that the findings of Sturman (2003) indicated that task complexity affects the relationship between time and performance. Specifically, Sturman found that low complexity task followed the inverted U-shaped time and performance relationship, but high complexity tasks did not.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that job experience, age and tenure are potential predictors of innovative work behavior; and they may affect job performance (Tierney & Farmer, 2002;Sturman, 2003). Table 3 displays the means, standard deviations, and correlations among the study variables.…”
Section: Control Variablesmentioning
confidence: 99%